2020
DOI: 10.1002/pld3.234
|View full text |Cite
|
Sign up to set email alerts
|

Drought‐induced protein (Di19‐3) plays a role in auxin signaling by interacting with IAA14 in Arabidopsis

Abstract: The members of early auxin response gene family, Aux/IAA, encode negative regulators of auxin signaling but play a central role in auxin‐mediated plant development. Here we report the interaction of an Aux/IAA protein, AtIAA14, with Drought‐induced‐19 (Di19‐3) protein and its possible role in auxin signaling. The Atdi19‐3 mutant seedlings develop short hypocotyl, both in light and dark, and are compromised in temperature‐induced hypocotyl elongation. The mutant plants accumulate more IAA and also show altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Recently, Di19 protein has been assigned to be involved in hormonal interactions in plant development. AtDi19-3 interacted with AtIAA14 as a positive regulator of auxin signaling and plays a role in some ethylene-mediated responses in Arabidopsis [ 26 ]. These studies suggested that Di19 family genes play crucial role in growth and development and abiotic stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Di19 protein has been assigned to be involved in hormonal interactions in plant development. AtDi19-3 interacted with AtIAA14 as a positive regulator of auxin signaling and plays a role in some ethylene-mediated responses in Arabidopsis [ 26 ]. These studies suggested that Di19 family genes play crucial role in growth and development and abiotic stress response.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to select potential candidate genes for cloning and functional verification using gene overexpression and CRISPR/Cas technology, a number of candidate genes were predicted based on propelling evidence from in silico and could be validated to unravel their actual regulatory role in the studied traits. For instance, recent evidence suggest that Auxin induced-like protein ( Zm00001d002374 ) predicted in the present study is reported to play a significant role under drought or heat and combined heat and drought stress in Arabidopsis [ 79 , 80 ]. Circadian clock and CARES are known to regulate gene expression under different conditions [ 81 ].…”
Section: Discussionmentioning
confidence: 84%
“…In ramie, we found their respective homologous genes, BnGMYB9 and BnGMYB 104 and their expression patterns were similar to those of AtMYB49/59 under cadmium treatment [69,70], so we deduced that they also had similar functions. BnGMYB45/89/90 which fall to the C33 group were according to phylogenetic analysis valuable candidate for abiotic stress [71][72][73]. Taken together, these above ndings might be valuable for improving the cadmium resistance of ramie via the manipulation of the BnGMYBs.…”
Section: Expression Pro Ling Of Bngr2r3-myb Genes With Rna-seq In Different Tissuesmentioning
confidence: 76%